PENGARUH KEBERBAKATAN MANAJERIAL TERHADAP EFEKTIVITAS ROTASI JABATAN ( STUDI KASUS PADA KANTOR POS DI REGIONAL IV JAKARTA) - Agung Surya Dwianto; Widayatmoko Widayatmoko ((JEMS) Jurnal Entrepreneur dan Manajemen Sains, 2021)
Job rotation is another way renew employee motivation. However, job rotation does not always go smoothly. It is possible that the job rotation plan that has been programmed by the company, causes protests from employees who feel that they are already established in their current position. Therefore, such a policy must be based on accurate data and information on individual performance. Another thing, it is important to consider that job rotation should be based on the competence of the employee concerned. They must be prepared in advance at least in the form of orientation at the new job site. It is so important to build a manager's competence, because a bad (incompetent) manager can have a bad impact on the company, and can even bring down the company. Therefore, companies need to pay attention to improving the quality of managers, in order to obtain appropriate competencies as expected by the company. Where one of the ways to develop and improve the competence of managers, is through job rotation. This study aims to analyze the effect of managerial competencies on job rotation at PT Pos Indonesia Regional IV Jakarta. The results showed that the managerial competencies variable had a significant positive effect on job rotation (p = 0.006). The fit model with existing data is based on the Goodness-of Fit Index criteria with the results of the Chi Square evaluation of 1100.906, with a significance level of 0.056 and the value of RMSEA (0.021), GFI (0.783), AGFI (0.762), CMIN / df (1.071), TLI (0.983) and CFI (0.984).Â Keywords: Managerial Competencies, Job Rotation